GLOBALIZACIÓN, EMPRESA Y ESTADO DE DERECHO EN EL PERú - Ugarte Vega Centeno, Máximo (2013)
The globalization brought us the internalization of the economy, in consequence the interdependency in the market, between countries, businesses and legal warranties for people who want to do economic activities. Nowaday the businesses have to face this phenomenon and take on the challenge as much internal as external environment. Also they have to adapt to the demands of the new consumers in the rule of Law.